FRI0037 IL-33 is over-expressed in the inflamed arteries of patients with giant cell arteritis. (23rd January 2014) - Ciccia, F.; Guggino, G.; Rizzo, A.; Giardina, A.; Alessandro, R.; Salvarani, C.; Triolo, G.
Abstract : Background: Giant-cell arteritis (GCA) is an inflammatorydisease of blood vessels most commonly involving large and medium arteriesof the head. Interleukin-33 (IL-33), a member of the IL-1 cytokine family [6], is a recently described novel activator of endothelial cells (ECs) which promotes adhesion molecules and proinflammatory cytokine expression in the endothelium, angiogenesis and vascular permeability in vitro and in vivo Objectives: To study the expression of IL-33 and to evaluate its relationship with macrophage polarization in artery biopsy specimens from patients with giant cell arteritis (GCA). Methods: IL-33 and ST2 tissue distribution was evaluated by immunohistochemistry. iNOS and CD163 were also used by immunohistochemistry to evaluate the M1 and M2 polarization, respectively. Quantitative gene expression analysis of IL-33, Th2-related transcription factor STAT6, Th2 cytokines (IL-4, IL-5, IL-25) and IFN-g was performed in artery biopsy samples obtained from 20 patients with GCA and 15 controls. Five additional patients who had received prednisone when the temporal artery biopsy was performed were also enrolled. Results: IFN-g and IL-33 were significantly over-expressed in the inflamed arteries of GCA patients. IL-33 over-expression was not accompanied by a concomitant increase of Th2 cytokines. Neovessels scattered through the inflammatory infiltrates were the main sites of IL-33 expression. The expression of IL-33 receptor ST2 was also increased in GCA patients. Arteries from glucocorticoid-treated patients had a lower expression of IL-33. IL-33 expression was accompanied by a clear M2 macrophages polarization. Conclusions: This is the first study demonstrating that expression of IL-33 and its receptor ST2 are increased in the inflamed arteries of GCA patients and appears to be suppressed in glucocorticoid treated patients. IL-33 in the inflamed arteries could act earlier in the artery inflammation promoting angiogenesis, vascular leakage and tissue infiltration by inflammatory cells. Disclosure of Interest: None Declared